Integrated analysis of behavioral, epigenetic, and gut microbiome analyses in App NL-G-F , App NL-F , and wild type mice - Payel Kundu (Nature Portfolio, 2021)
Abstract Epigenetic mechanisms occurring in the brain as well as alterations in the gut microbiome composition might contribute to Alzheimer’s disease (AD). Human amyloid precursor protein knock-in (KI) mice contain the Swedish and Iberian mutations (App NL-F ) or those two and also the Arctic mutation (App NL-G-F ). In this study, we assessed whether behavioral and cognitive performance in 6-month-old App NL-F , App NL-G-F , and C57BL/6J wild-type (WT) mice was associated with the gut microbiome, and whether the genotype modulates this association. The genotype effects observed in behavioral tests were test-dependent. The biodiversity and composition of the gut microbiome linked to various aspects of mouse behavioral and cognitive performance but differences in genotype modulated these relationships. These genotype-dependent associations include members of the Lachnospiraceae and Ruminococcaceae families. In a subset of female mice, we assessed DNA methylation in the hippocampus and investigated whether alterations in hippocampal DNA methylation were associated with the gut microbiome. Among other differentially methylated regions, we identified a 1 Kb region that overlapped ing 3′UTR of the Tomm40 gene and the promoter region of the Apoe gene that and was significantly more methylated in the hippocampus of App NL-G-F than WT mice. The integrated gut microbiome hippocampal DNA methylation analysis revealed a positive relationship between amplicon sequence variants (ASVs) within the Lachnospiraceae family and methylation at the Apoe gene. Hence, these microbes may elicit an impact on AD-relevant behavioral and cognitive performance via epigenetic changes in AD-susceptibility genes in neural tissue or that such changes in the epigenome can elicit alterations in intestinal physiology that affect the growth of these taxa in the gut microbiome.